Globalizacja i regionalizacja - współzależne zjawiska determinujące ramy funkcjonowania współczesnych przedsiębiorstw - Adamczyk, Jan (Globalisation and Regionalism - Coherent Phenomena That Determine Functioning of Modern Companies, 2006)
The article presents the concept of two as it seems antagonist phenomena: globalisation and regionalism. They mainly shape the word economy specifying the framework within functioning of modern companies. At the beginning the definitions of analysed notions have been presented, describing then relationships between globalization and regionalism.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 211-217